Osteocalcin is not a strong determinant of serum testosterone and sperm count in men from infertile couples. (22nd May 2013) - Schwetz, V.; Gumpold, R.; Graupp, M.; Hacker, N.; Schweighofer, N.; Trummer, O.; Pieber, T. R.; Ballon, M.; Lerchbaum, E.; Obermayer‐Pietsch, B.
Summary Osteocalcin (OC) – released by osteoblasts and known as a marker of bone turnover – has been suggested to influence male fertility in murine models by enhancing testosterone production and sperm count. Results from clinical studies are scarce, however. The aim of this cross‐sectional study was to investigate the proposed association of OC, undercarboxylated osteocalcin (ucOC) or carboxylated osteocalcin (cOC) with testosterone and sperm count in a cohort of 159 young male adults from infertile couples. Semen analysis was performed. Testosterone, free testosterone, LH, OC and ucOC were measured in serum samples after an overnight fast. cOC and OC correlated weakly but significantly with testosterone (OC: r = 0.165, p = 0.040, cOC: r = 0.193, p = 0.017), but not after adjusting for age and body mass index (BMI) or waist–hip ratio (WHR). %ucOC (ucOC levels expressed as percentage of total OC) correlated inversely with LH (r = −0.184, p = 0.023) and remained significant after the same adjustment. No significant correlations were observed between OC, cOC, ucOC, %ucOC and sperm count, semen volume and number of vital spermatozoa. In binary logistic regression analyses, none of the parameters of OC were predictors of oligozoospermia after adjusting for age and BMI or WHR. The weak association between %ucOC and LH has marginal clinical importance because of the lack of associations of parameters of OC with testosterone and sperm count. The current data thus cannot support the notion that OC is associated with male fertility in young men from infertile couples.